1987
DOI: 10.1177/096032718700600408
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effect of Decimal and Centesimal Dilutions of Arsenic on the Retention and Mobilization of Arsenic in the Rat

Abstract: Having developed a pharmacokinetic method for studying the fate of orally administered arsenious anhydride by a radioactive tracer method, the influence of Hahnemannian dilutions of arsenicum album on the elimination and retention of this toxin in the rat was then investigated. The effects of centesimal (cH) and decimal (dH) dilutions were studied. All the dilutions studied were found to be active. The strongest effects were observed after the administration of dilutions correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 0 publications
1
32
0
1
Order By: Relevance
“…The present experiment was performed to investigate if there is a role for the use of isomers in homeopathy, and more specifically to see if the toxic effects of optically active substances may be counteracted by the administration of potentized preparations of their isomers and more specifically of their enantiomers. Experiments using isopathy have been previously reported [12][13][14][15][16][17][18][19][20][21]. In isopathy one is trying to treat the toxic, pathological or physiological effects of a substance by administering a diluted or potentized form of the same substance.…”
Section: Introductionmentioning
confidence: 99%
“…The present experiment was performed to investigate if there is a role for the use of isomers in homeopathy, and more specifically to see if the toxic effects of optically active substances may be counteracted by the administration of potentized preparations of their isomers and more specifically of their enantiomers. Experiments using isopathy have been previously reported [12][13][14][15][16][17][18][19][20][21]. In isopathy one is trying to treat the toxic, pathological or physiological effects of a substance by administering a diluted or potentized form of the same substance.…”
Section: Introductionmentioning
confidence: 99%
“…High dilutions of cycloheximde (10 -27 M) also protected against the effects of glutamate exposure [35]. -Using a radioactive tracer method high dilutions of As 2 O 3 (10 -14 g/l) enhanced the elimination of orally administered arsenious anhydride [36].…”
Section: Discussionmentioning
confidence: 99%
“…Change using tautopathic ultra molecular dilutions of lead and arsenic have been demonstrated in animal studies: lead [2][3][4][5]; arsenic [6][7][8][9][10][11][12]. Two pilot studies describe symptom reduction in patients with lead exposure [13] and groundwater arsenic contamination [14] No studies of the tautopathic use of cannabis were found.…”
Section: Introductionmentioning
confidence: 99%